Cestodes of bats from the National Park Cerros de Amotape, Tumbes, Peru - Vargas, Marina (2009)
In September 2006, at Parque Nacional Cerros de Amotape, department of Tumbes, Peru, 39 individuals of bats belonging to 16 species were captured. Parasitological analysis determined that only two individuals of the species Phyllostomus hastatus (Phyllostomidae) and Noctilio leporinus (Noctilionidae) were parasitized. The cestodes were collected from the small intestine and identified as Atriotaenia hastati Vaucher, 1982 (Anoplocephalidae) and Vampirolepis sp. (Hymenolepididae). Atriotaenia hastati is a new record for Peru and Vampirolepis sp. is registered for the first time in Tumbes and a new host, Noctilio leporinus.